Rocks and shards: geoarchaeology and palaeoenvironments of the Al-Rustaq Manaqi Archaeological Complex in north-central Oman - Chlachula, Jiri; Hesein, Mohamed; Gernez, Guillaume; Douglas, Khaled; Michniewicz, Jacek; Al-Jahwari, Nasser (Geologos, 2026)
The present study discusses the results of geological and geoarchaeological research at Manaqi in Al-Rustaq, the new Iron Age (1300–300 BC) complex in north-central Oman. The regional relief attests to pronounced geo-environmental dynamics, largely linked to orogeny of the central Jabal Akhdar Range, as well as climate change. The investigated prehistoric site provides evidence of multiple phases of occupation, the earliest being represented by numerous stone tools, documenting a sequenced presence of Palaeolithic people in the vicinity of an ancient fluvial channel. The principal Iron Age site with residential buildings, tombs and other architectural elements (defensive, irrigation, stone-mining) bear witness to a well-organised settlement with distinct areas, suggesting specific functions. The size and layout of households and funerary structures built from local bedrock and alluvial boulders point to social complexity of a semi-sedentary society. The spatial organisation and internal arrangement of the Manaqi Site suggest that its economic significance was likely linked to an ancient trade route along the present Wadi Al-Fara, connecting the Al-Hajar Mountains with the coast of the Sea of Oman. The synthesized field and analytical data provide a geo-contextual background for the regional pre-Islamic settlements within the South Batinah Governorate. The Manaqi locality also represents a most interesting geo-site, illustrating a multi-facetted geological and palaeoenvironmental history of the present rocky desert subjected to active geomorphic modelling with an ancient anthropogenic imprint. Climate was a key factor in controlling the rise of pre-Islamic civilisation in the Oman Sultanate.